Jean-Antoine Chaptal (1756–1832), agronome et chimiste - Fournier, Josette (Comptes Rendus. Chimie)
This year, the academic world is celebrating the two hundredth anniversary of the publication of the last major work by Jean-Antoine Chaptal (1756–1832). A doctor, manufacturer, agronomist, professor, scholar, economist, statesman and senior minister under the Consulate, Chaptal was a provincial and a Parisian who lived through a variety of political regimes, from the Ancien Régime to the July Monarchy, via the Convention, the Directoire, the Consulate, the First Empire and the Restoration. He embraced several schools of thought, from the Encyclopaedists to the Saint-Simonians. The chemist is remembered for his work on wine, the bleaching and dyeing of cotton, and the extraction of beet sugar. This manuscript is divided into two main parts, dealing successively with Jean-Antoine Chaptal’s student years until his appointment to the Consulate’s Ministry of the Interior, and then with the period from the Consulate to the July Monarchy.